Endocrine Disorders that Cause Diabetes - Rehan Naqvi (International Journal of Integrative Research, 2023)
Endocrine disorders are a scientific group of conditions that affect the day-to-day functioning of the endocrine system, which is responsible for producing and regulating hormones in the body. Many endocrine problems can lead to the development of diabetes, a metabolic disorder characterized by persistently high blood sugar levels. Excess cortisol can cause insulin resistance, which causes an increase in blood sugar levels, and eventually leads to diabetes. Another disease is acromegaly which is caused by an overproduction of increased hormones. An extended hormone boom stage can lead to insulin resistance in the long term, contributing to an increase in diabetes. Polycystic ovary syndrome (PCOS) is an endocrine disease commonly associated with insulin resistance and diabetes. PCOS is characterized by an imbalance of hormones, especially androgens. This imbalance can impair insulin signaling, especially insulin resistance, and the subsequent development of diabetes. Hypothyroidism, which is characterized by low thyroid hormone levels, can lead to insulin resistance and impaired insulin secretion. In contrast, hyperthyroidism, which is characterized by overproduction of thyroid hormone, can increase glucose metabolism and lead to diabetes in susceptible individuals. In addition, tumors of the endocrine system, including insulinomas and glucagonomas, can cause atypical insulin production and release, leading to hypoglycemia and hyperglycemia, respectively.